INSTRUMEN PENILAIAN BAHASA ARAB DI ERA DIGITAL - Syamfa Agny Anggara, Mustahar Ali Wardana (PRODI PAI FIK UNIRA MALANG, 2024)
In the digital era, a variety of new assessment instruments are being introduced. An example is the use of online learning platforms that allow teachers to give assignments, exams, or quizzes online. This type of research is a type of literature study research by studying various reference books and similar previous research results. The results showed that a variety of Arabic assessment instruments in the digital era that were widely developed include online tests, portfolios. The use of technology in assessment can improve the efficiency, accuracy, and objectivity of assessment.